SERAPAN DAN KETAHANAN AZOLLA TERHADAP KROMIUM PADA VERTISOLS DAN ENTISOLS DENGAN BERBAGAI TINGGI GENANGAN AIR - Sudadi Sudadi; Dwi Priyo Ariyanto; Erwin Purniawati (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2009)
Title : The Uptake and Tolerance of Azolla to Chromium on Vertisols and Entisols at Various Water Levels. This research aims to study the effect of water level, soil kind, chromium concentration (Cr), and their interactions on uptake and tolerance of azolla to Cr. The research was done in March to May 2009 in the green house of Faculty of Agriculture, Sebelas Maret University, Surakarta. The research used completely randomized design (CRD) factorial with three treatment factors, they were: soil kind (Vertisols of Jatikuwung and Entisols Colomadu, Karanganyar), water levels (0; 2; and 7 cm) and Cr concentrations (0; 5; 10; 15; and 20 ppm). There were 191 g of Vertisols and 200 g of Entisols pass to 2 mm sieve put into plastic pot and watering at various levels according to the treatments. A gram of fresh azolla was spread on each pot and incubated for three weeks. Each treatment combinations were replicated three times. Sampling was taken at 1, 2, and 3 weeks after planting for azolla biomass, Cr uptake of azolla, available Cr, and Cr toxicities symptoms of azolla. The data analyzed statistically by Kruskal Wallis test at 95% level significant, followed with Mood Median test. The result shows that soil kind has no significant effect, while water level, Cr concentration, and treatment interaction contribute highly significant influence on uptake and tolerance of azolla to Cr. The highest uptake of Cr at the Vertisols was taken at 7 cm water level and 15 ppm Cr concentration, while at the Entisols was in 2 cm of water level and 15 ppm Cr concentration. Azolla most tolerance to Cr at treatment combination of 2 cm water level and 10 ppm Cr concentration in Vertisols, and at 2 cm water level and 5 ppm Cr concentration at Entisols. Keywords: A. mycrophylla, chromium, Cr uptake and tolerance, water level